Sisi Terang dan Gelap Narsisme CEO: Analisis Tinjauan Pustaka Sistematis - Ruth Stephanie Tambun (Politeknik Ganesha Medan, 2026)
The topic of CEO characteristics that is being discussed is CEO narcissism. This study aims to analyze the impact of CEO narcissism on company performance and reveal the good and bad sides of CEO narcissism through a systematic literature review of 56 articles indexed by Scopus and Sinta. The results of the literature review show that there is still inconsistency in the results of research on the application of narcissistic CEOs to company performance. The good side of CEO narcissism is conservative, innovative, internationalization, and strategic and appropriate decision making. The bad side of CEO narcissism is opportunism, self-oriented and abusive leadership style, which increases tax avoidance, weakens internal supervision, and increases debt financing. Companies need effective and efficient supervision of CEO narcissism and risk management. Companies must also ensure that the company's work culture is not influenced by the bad side of CEO narcissism. Further research is needed to understand the long-term impact of narcissistic leadership styles, the best mitigation mechanisms, and differences in the influence of CEO narcissism across cultural and industrial contexts.